Frequency of Subclinical Hypothyroidism in Non Hemodialysis Dependent CKD - Sarwar, Abeera; Jabeen, Rukhshanda; Budhani, Anoshi; Asnani, Sadhna; Samreen, Soha; Kumari, Soha (Indus Journal of Bioscience Research, 2025)
Background: Chronic kidney disease (CKD) is a progressive disorder that affects several body systems, including endocrine function. Alterations in thyroid hormone metabolism are often reported in patients with reduced kidney function. This study aimed to determine the frequency of subclinical hypothyroidism (SCH) among patients with non-hemodialysis dependent CKD and to examine factors associated with its occurrence. Methods: This cross-sectional study included 256 patients diagnosed with non-hemodialysis dependent CKD. Demographic information, clinical characteristics, and laboratory findings were recorded. Thyroid function was assessed by measuring serum thyroid-stimulating hormone (TSH) and free thyroxine levels. SCH was defined as elevated TSH with normal free thyroxine. Statistical analysis was performed to explore the relationship between SCH and patient characteristics, with p < 0.05 considered statistically significant. Results: Most participants were aged 51–70 years (68.4%), and males and females were almost equally represented. The overall frequency of subclinical hypothyroidism was 32.4%. No significant association was observed between SCH and age, gender, duration of CKD, diabetes mellitus, or hypertension. However, body mass index (p = 0.01) and stage of CKD (p = 0.01) showed significant relationships with SCH. The proportion of SCH increased with worsening kidney function, from 25.8% in stage 3 CKD to 39.5% in stage 4 CKD. Conclusion: Subclinical hypothyroidism was commonly observed among patients with non-hemodialysis dependent CKD. These findings suggest that evaluating thyroid function may be useful during routine assessment of CKD patients, particularly as kidney disease progresses.